Reconstructing Wasathiyyah Moderation: The Thought of Abdurrahman Al-Sudais and Its Application in Indonesian Islamic Higher Education - Mufid Mufid; Maemunah Sadiyah; Adian Husaini; Akhmad Alim (Equivalent: Jurnal Ilmiah Sosial Teknik, 2026)
Background: Breeding grounds for radicalism and extreme liberalism on Indonesian university campuses continue to endanger religious education cohesion, while Islamic higher education institutions mired in the fragmentation of different-flavored ideologies without moderation policies worsen polarization among students. This circumstance emphasizes the absolute requirement for an integrated wasathiyyah framework in PAI curriculum. Objective: The objective of this study is to analyze the conception of Abdurrahman Al-Sudais about wasathiyyah as stated in Bulugh al-Amal fi Tahqiq al-Wasatthiyah wa al-Itidal and its implementation in PAI curriculum design in Indonesian Islamic higher education institutions. Method: This is a qualitative study using library research and a descriptive-interpretive (hermeneutical) approach. The data were collected through content analysis of the dominant text and participant observation via case studies on STID Mohammad Natsir Bekasi and STAI Al-Hidayah Bogor, and then analyzed using the Miles and Huberman model. Results: It turns out that Al-Sudais's wasathiyyah is based on tawassuth (42%), i'tidal (35%), and tasamuh (23%), as grounded in QS. Al-Baqarah: 143. All of these values are internalized in a number of courses that exist in PAI, namely through Islamic Religious Moderation Houses (Rumah Moderasi Beragama) and various community service programs (KKN), which actively reduce intolerance and foster inclusive religious attitudes. Conclusions: Al-Sudais's framework offers a researchable, empirically based model of PAI development that strengthens religious moderation, encourages inter-religious harmony, and prepares a balanced generation to face Indonesia's pluralistic community.